2013
DOI: 10.1111/myc.12146
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides brasiliensis infection in domestic rabbits (Oryctolagus cuniculus)

Abstract: The objective of this study was to evaluate the infection of domestic rabbits by Paracoccidioides brasiliensis. Initially two rabbits were experimentally infected with P. brasiliensis and the humoral immune response was evaluated by ELISA using gp43 as antigen. The two animals showed IgG response against gp43 although no signs of disease were observed. The seroepidemiological study was carried out in 170 rabbits (free range n = 81 and caged n = 89) living in an endemic area for human paracoccidioidomycosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
(78 reference statements)
0
5
0
1
Order By: Relevance
“…Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil. The present study reinforces that ELISA is a useful method for detection of P. brasiliensis infection in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our research group showed high rates of gp43 ELISA positivity in dogs [6], horses [9], sheep [12], goats [13], pigs [29], rabbits [30] and wild monkeys [15] from Paraná State, Brazil. The present study reinforces that ELISA is a useful method for detection of P. brasiliensis infection in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Intradermal and serological tests conducted on domestic and free or captive wild animals have revealed that various mammals and birds may be infected with Paracoccidioides spp. [ 66 , 67 , 68 ]. It was observed that the rate of infection is higher in dogs from the rural area than in dogs from the urban zone and higher in rabbits raised free than in caged animals [ 66 , 69 ].…”
Section: Paracoccidioidomycosis-infectionmentioning
confidence: 99%
“…[ 66 , 67 , 68 ]. It was observed that the rate of infection is higher in dogs from the rural area than in dogs from the urban zone and higher in rabbits raised free than in caged animals [ 66 , 69 ]. Part of the animals reacting to the tests was sacrificed and Paracoccidioides spp.…”
Section: Paracoccidioidomycosis-infectionmentioning
confidence: 99%
“…Dogs living in the rural area have a higher rate of infection than dogs living in the urban area 37 . Freely raised rabbits have higher rates of infection than caged animals and 83% of the rabbits exposed to natural infection develop antibodies against P. brasiliensis 7 . However, no lesions caused by P. brasiliensis have been detected in anatomopathological exams of animals reactive to antigens of the fungus in serological or skin tests 37 .…”
Section: Introductionmentioning
confidence: 99%